Imobilisasi Biomasa Cocodust Dengan Silika Gel Sebagai Adsorben Ion Cd(II) dan Pb(II) Dalam Larutan - Tri Endah W (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
It has been studied cocodust immobilization with silika gel as adsorbent of heavy metal Cd(II) and Pb(II) ions in solution using batch metode. Adsorbent material characterizations obtained were performed with using Scanning Electron Microscope (SEM)- Energy Dispersive X-ray Spectrophotometer (EDS) to observe surface morphology of adsorbent and element composition existed in material resulted from immobilization. Analisys of adsorbent material functional group was carried out with using IR and determination of Cd(II) and Pb(II) ions concentration was applied with using atomic adsorption spectrofotometer (AAS). Adsorbent characterization result by infrared spectrophotometer (IR) shows that functional group of –OH, C=O, Si-O-Si, and C-H are exist on adsorbent. In addition, adsorbent characterizations by SEM-EDS proves the existency of Si, O, and C element on adsorbent. Adsorption process of Cd(II) and Pb(II) ions is optimum at pH 6 with contact time of 60 minutes. Adsorption process of Cd(II) and Pb(II) ions on cocodust biomass tends to follow second orde pseudo kinetic and Freundlich adsorption isoterm model with concentration of Cd(II) and Pb(II) ions adsorbed each 17.91 and 23.64 mg g-1.